Neutralization of organophosphate over highly dispersed Fe, Cu, and Co on silica - Katelyn R. Alley; Quinn C. Cunneen; Dario Prieto-Centurion (Catalysis Communications, 2021)
Organophosphates are highly toxic compounds used as pesticides and chemical warfare agents. Herein, we describe SiO2-supported Fe, Co, and Cu catalysts that degrade organophosphate pesticide malathion at mild temperatures in the presence of H2O2. These catalysts are prepared by impregnation of SiO2 with solutions of bulky metal chelates that promote dispersion and low coordination, as shown spectroscopically. Turnover frequencies of catalysts prepared from chelated precursors are higher than those of controls prepared from nitrates and oxides, and independent of metal loading. The latter indicates equal activity and accessibility of active sites and suggests invariant structure in the loading range studied.